Analisis Konvergensi Hukum Ekonomi Internasional: Tantangan Hukum Bagi Indonesia Dalam Mengharmonisasikan Kepentingan Brics Dan Asean - Quddus, Muh. Syah Quddus (Equality : Jurnal Hukum dan Keadilan, 2025)
Indonesia's membership in BRICS and ASEAN provides great opportunities in trade, investment, and diplomacy, but faces the challenge of economic law harmonization between the two blocs. BRICS focuses on protectionism and infrastructure, while ASEAN promotes free market integration creating complexity for Indonesia in maintaining the balance of national and international policies. The development of a flexible yet robust legal framework is necessary to manage the dynamics of regulatory differences in the two organizations without compromising Indonesia's sovereignty. This research aims to analyze the legal strategies that Indonesia can implement to overcome the challenges of international economic regulatory harmonization between BRICS and ASEAN. The method used in this research is juridical-normative research, by analyzing secondary data from primary, secondary, and tertiary legal materials.  The results show that Indonesia plays a strategic role in bridging economic law conflicts between BRICS and ASEAN which have different economic principles where BRICS supports protectionism, while ASEAN encourages market liberalization. Indonesia's membership in both blocs creates challenges in regulatory harmonization, especially when Indonesia is also involved in multilateral agreements such as WTO and G20. By capitalizing on its position, Indonesia can strengthen its economy and influence global policies while maintaining national economic legal sovereignty.